Glycogen synthase kinase-3 inhibition attenuates fibroblast activation and development of fibrosis following renal ischemia-reperfusion in mice - Shailendra P. Singh; Shixin Tao; Timothy A. Fields; Sydney Webb; Raymond C. Harris; Reena Rao (The Company of Biologists, 2015)
Glycogen synthase kinase-3β (GSK3β) is a serine/threonine protein kinase that plays an important role in renal tubular injury and regeneration in acute kidney injury. However, its role in the development of renal fibrosis, often a long-term consequence of acute kidney injury, is unknown. Using a mouse model of renal fibrosis induced by ischemia-reperfusion injury, we demonstrate increased GSK3β expression and activity in fibrotic kidneys, and its presence in myofibroblasts in addition to tubular epithelial cells. Pharmacological inhibition of GSK3 using TDZD-8 starting before or after ischemia-reperfusion significantly suppressed renal fibrosis by reducing the myofibroblast population, collagen-1 and fibronectin deposition, inflammatory cytokines, and macrophage infiltration. GSK3 inhibition in vivo reduced TGF-β1, SMAD3 activation and plasminogen activator inhibitor-1 levels. Consistently in vitro, TGF-β1 treatment increased GSK3β expression and GSK3 inhibition abolished TGF-β1-induced SMAD3 activation and α-smooth muscle actin (α-SMA) expression in cultured renal fibroblasts. Importantly, overexpression of constitutively active GSK3β stimulated α-SMA expression even in the absence of TGF-β1 treatment. These results suggest that TGF-β regulates GSK3β, which in turn is important for TGF-β-SMAD3 signaling and fibroblast-to-myofibroblast differentiation. Overall, these studies demonstrate that GSK3 could promote renal fibrosis by activation of TGF-β signaling and the use of GSK3 inhibitors might represent a novel therapeutic approach for progressive renal fibrosis that develops as a consequence of acute kidney injury.